Total molecular gas masses of Planck – Herschel selected strongly lensed hyper luminous infrared galaxies. Issue 3 (25th November 2017) - Harrington, K C; Yun, M S; Magnelli, B; Frayer, D T; Karim, A; Weiß, A; Riechers, D; Jiménez-Andrade, E F; Berman, D; Lowenthal, J; Bertoldi, F
Abstract: We report the detection of CO(1–0) line emission from seven Planck and Herschel selected hyper luminous (${L_{\rm IR (8{\rm -}1000{μ m})} > 10^{13}\, \, {\rm L}_{{\odot }} }$ ) infrared galaxies with the Green Bank Telescope (GBT). CO(1–0) measurements are a vital tool to trace the bulk molecular gas mass across all redshifts. Our results place tight constraints on the total gas content of these most apparently luminous high- z star-forming galaxies (apparent IR luminosities of L IR > 10 13 − 14 L⊙ ), while we confirm their predetermined redshifts measured using the Large Millimeter Telescope, LMT ( z CO = 1.33–3.26). The CO(1–0) lines show similar profiles as compared to J up = 2–4 transitions previously observed with the LMT. We report enhanced infrared to CO line luminosity ratios of $\langle L_{\rm IR} / L^{′ }_{\rm CO(1{\rm -}0)} \rangle \ = 110 ± 22 {\, }\, \, {\rm L_{{\odot }} (K {\, } km {\, } s^{-1} {\, } pc^{-2})^{-1} }$ compared to normal star-forming galaxies, yet similar to those of well-studied IR-luminous galaxies at high- z . We find average brightness temperature ratios of 〈 r 21 〉 = 0.93 (2 sources), 〈 r 31 〉 = 0.34 (5 sources), and 〈 r 41 〉 = 0.18 (1 source). The r 31 and r 41 values are roughly half the average values for SMGs. We estimate the total gas mass content as ${\rm μ M_{H2} = (0.9{\rm -}27.2) × 10^{11} (α _{\rm CO}/0.8){\, }{\rm M}_{{\odot }}}$, where μ is the magnification factor and αCO is the CO line luminosity to molecular hydrogen gas mass conversion factor. The rapid gas depletion times, ${\rm \langle τ _{\rm depl} \rangle = 80}$ Myr, reveal vigorous starburst activity, and contrast the Gyr depletion time-scales observed in local, normal star-forming galaxies.